Transmission of Infectious Vibrio cholerae through Drinking Water among the Household Contacts of Cholera Patients (CHoBI7 Trial) - Rafique, Raisa; Rashid, Mahamud-ur; Monira, Shirajum; Rahman, Zillur; Mahmud, Md. Toslim; Mustafiz, Munshi; Saif-Ur-Rahman, K. M.; Johura, Fatema-Tuz; Islam, Saiful; Parvin, Tahmina; Bhuyian, Md. Sazzadul I.; Sharif, Mohsena B.; et al. (Frontiers in Microbiology, 2016)
Recurrent cholera causes significant morbidity and mortality among the growing population of Dhaka, the capital city of Bangladesh. Previous studies have demonstrated that household contacts of cholera patients are at >100 times higher risk of cholera during the week after the presentation of the index patient. Our prospective study investigated the mode of transmission of Vibrio cholerae, the cause of cholera, in the households of cholera patients in Dhaka city. Of total 420 rectal swab samples analyzed from 84 household contacts and 330 water samples collected from 33 households, V. cholerae was isolated from 20%(17/84) of household contacts, 18%(6/33) of stored drinking water, and 27%(9/33) of source water samples. Phenotypic and molecular analyses results confirmed the V. cholerae isolates to be toxigenic and belonging to serogroup O1 biotype El Tor (ET) possessing cholera toxin of classical biotype (altered ET). Phylogenetic analysis by pulsed-field gel electrophoresis (PFGE) showed the V. cholerae isolates to be clonally linked, as >95% similarity was confirmed by sub-clustering patterns in the PFGE (NotI)-based dendrogram. Mapping results showed cholera patients to be widely distributed across 25 police stations with the highest incidence in households near the major rivers and polluted water bodies. The data presented on the transmission of infectious V. cholerae within the household contacts of cholera patients through drinking water underscores the need for safe water to prevent spread of cholera and related deaths in Dhaka city.